Preparation method of polysilicate aluminum chloride flocculant

By optimizing the synthesis process of polyaluminum silicate chloride flocculant, including adjusting the molar ratio of sodium silicate and aluminum salt and adding stabilizers, the problem of reduced stability and solubility of flocculant under low temperature and low turbidity conditions is solved, and the problem of reduction of flocculant stability and solubility under low temperature and low turbidity conditions is achieved. Efficient treatment of tap water and water quality stability in winter.

CN119219045AInactive Publication Date: 2024-12-31MUDANJIANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411365691.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Under low temperature and low turbid conditions, the stability and solubility of the flocculant are reduced, which affects the flocculation effect. The stability of the existing polyaluminum silicate flocculants is poor, making it difficult to meet the needs of tap water treatment in winter.

Method used

Optimize polysilicate chlorination by adjusting the molar ratio of sodium silicate and aluminum salt, controlling the pH value, adding stabilizers such as disodium hydrogen phosphate, sodium citrate or potassium biphthalate, and performing high-speed stirring at high temperatures, optimizing polysilicate chlorination The synthesis process of aluminum flocculant improves its stability and adaptability.

Benefits of technology

It significantly improves the stability and flocculation performance of polyaluminum silicate flocculant, so that it can effectively treat tap water under low temperature and low turbid conditions, extends the service life of the flocculant, and ensures that the water quality meets the standards.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of a polysilicate aluminum chloride flocculant, and belongs to the technical field of flocculants. The method comprises the following steps: firstly, adding an acid solution into a sodium silicate aqueous solution, regulating and controlling the pH value, stirring and activating, and standing to obtain a polysilicic acid solution; adding the polyaluminum chloride solution into the polysilicic acid solution, heating and stirring at a high speed to obtain a polysilicic acid aluminum chloride solution; and finally, adding a stabilizer into the polysilicate aluminum chloride solution to obtain the polysilicate aluminum chloride flocculant. According to the method, the synthesis process and the stabilization time of the polysilicate aluminum chloride flocculant are optimized and prolonged, so that the high-efficiency treatment of 0 DEG C tap water source water in winter is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flocculants, and in particular relates to a method for preparing a polyaluminium silicate chloride flocculant. Background Art

[0002] The treatment of source water by water plants usually includes steps such as sedimentation, filtration, disinfection and flocculation. Among them, flocculation is the key link, which ensures the clarity and transparency of water quality. The advantage of flocculation lies in its high efficiency: flocculants quickly combine with suspended matter and colloids in the water, condensing them into large particles, which are then convenient for sedimentation and filtration. In addition, the reliability of flocculants cannot be ignored. It ensures the stability of water quality, reduces the content of suspended matter and colloids, and significantly improves water quality standards. What is more worth mentioning is that flocculants have high chemical stability, are harmless to the human body, and are also friendly to the environment.

[0003] However, when winter comes, the source water temperature drops to 0℃, and its characteristics change to low temperature and low turbidity. At this time, the application of flocculants faces some challenges: First, the viscosity of water increases and the fluidity becomes worse in a low temperature environment, making it difficult for fine particles to combine. This slows down the flocculation speed and the sedimentation rate of particles. In addition, low temperature will also affect the hydrolysis reaction of the coagulant, slowing down its speed, thereby affecting the flocculation effect. Secondly, the concentration of suspended matter and colloidal particles in low-turbidity source water is low, which reduces the probability of collision between particles and is not conducive to coagulation. At the same time, due to the complexity of impurity components, it becomes particularly important to select and use suitable flocculants. Finally, in low-temperature and low-turbidity source water, the stability of the flocculant may be affected, resulting in a decrease in its solubility and stability in water, thereby affecting its flocculation effect. Some flocculants may also react with impurities in the water to produce precipitation or reduce the flocculation effect.

[0004] In summary, although flocculants have significant effects in treating source water, they still have some limitations when treating low-temperature, low-turbidity source water at 0°C in winter. Therefore, in order to ensure water quality, it may be necessary to adjust the treatment process or select flocculants that are more suitable for low-temperature conditions. At the same time, it is also necessary to strengthen the research on the stability and solubility of flocculants to improve their treatment effect and service life.

[0005] There are many types of flocculants, which are generally divided into four categories: inorganic flocculants, organic flocculants, microbial flocculants and composite flocculants. Among them, inorganic flocculants are widely used in tap water treatment due to their advantages such as easy raw materials, simple process, low cost and low toxicity. At present, polyaluminum silicate chloride is the most widely used inorganic polymer flocculant. It has a good flocculation effect and can effectively remove suspended matter and colloids in water. Polyaluminum silicate chloride is a complex of polysilicate and metal salts developed on the basis of polysilicate and traditional inorganic flocculants such as aluminum salts and iron salts. It is a new type of composite inorganic polymer flocculant developed in recent years. It has both electrical neutralization and adsorption bridging effects. Due to its good flocculation effect, special effect in treating low-temperature and low-turbidity water, and low price, it has attracted great attention in the water treatment industry.

[0006] There are two methods for preparing polysilicate aluminum salts: the first method is to introduce aluminum salts into polysilicate solution. The polysilicate aluminum salt flocculant prepared by this method has a higher molecular weight and has a stronger adsorption bridging ability and electrical neutralization ability for colloidal substances in water. However, due to the easy gelation of polysilicate, the stability of the flocculant is poor, so this flocculant is only suitable for immediate use. The second method is to synthesize raw materials such as sodium silicate, sodium aluminate and aluminum sulfate using a high shear process. Through this method, a basic multi-nuclear hydroxy polysilicate aluminum salt flocculant with excellent performance can be prepared. However, this preparation process is relatively complicated and has high requirements for raw materials and equipment, so it is difficult to promote in practical applications.

[0007] In order to improve the stability of polyaluminium silicate flocculants, it can be achieved by improving the synthesis scheme and adding stabilizers. In addition, by adding stabilizers such as anhydrous ethanol, acetone, surfactants, etc., the stability time of the flocculant can also be extended to a certain extent. In addition to the above methods, the speed of the polymerization reaction and the product performance can also be optimized by adjusting the concentration, mixing ratio, reaction temperature, pH value, metal ions and storage temperature of the raw materials. These conditions have an important influence on the performance and stability of the flocculant, so they need to be fully considered in practical applications. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a polyaluminium silicate chloroflocculant, which optimizes and prolongs the synthesis process and stabilization time of the polyaluminium silicate chloroflocculant to achieve efficient treatment of 0°C tap water source water in winter.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] The present invention provides a method for preparing a polyaluminium chloride silicate flocculant, comprising:

[0011] Step 1: adding the acid solution to the sodium silicate aqueous solution, adjusting the pH value, stirring and activating, and then standing to obtain a polysilicic acid solution;

[0012] Step 2: adding the polyaluminium chloride solution to the polysilicic acid solution, heating and stirring at high speed to obtain a polysilicic acid aluminium chloride solution;

[0013] Step 3: adding a stabilizer to the polyaluminium chloride solution obtained in step 2 to obtain a polyaluminium chloride flocculant.

[0014] Preferably, the acid solution in step 1 is hydrochloric acid.

[0015] Preferably, the SiO2% content in the sodium silicate aqueous solution described in step 1 is 2.0%.

[0016] Preferably, the pH value in step 1 is controlled at 3.0-4.0.

[0017] Preferably, the stirring activation time in step 1 is 10 min-30 min.

[0018] Preferably, in step 2, the polyaluminium chloride solution is added at an Al / SiO2 molar ratio of 1.0-2.0.

[0019] Preferably, the heating temperature in step 2 is 65-75° C., and the stirring speed is 900-1100 r / min.

[0020] Preferably, the stabilizer in step three is a solid stabilizer or a liquid stabilizer.

[0021] Preferably, the fixing stabilizer includes one or more of disodium hydrogen phosphate, sodium citrate or potassium hydrogen phthalate.

[0022] Preferably, the liquid stabilizer comprises one or more of 10% NaOH solution, saturated sodium acetate solution, 0.1 mol / L potassium hydrogen phthalate solution or saturated sodium bicarbonate solution.

[0023] Beneficial effects of the present invention

[0024] The present invention provides a preparation method of a polysilicate aluminum chloride flocculant. Compared with the prior art, the present invention has made many innovations and optimizations in the synthesis and stability improvement of the polysilicate aluminum chloride flocculant: first, according to the characteristics of anions in aluminum salts, a suitable acid is selected to accurately adjust the pH value to ensure the initial stability of the flocculant. Secondly, by increasing the reaction temperature, the stability of the flocculant is further enhanced, so that it can maintain excellent performance under various environmental conditions. In addition, a variety of stabilizers are added to effectively extend the stability time of polysilicate aluminum chloride, making it more suitable for low-temperature and low-turbidity source water treatment at 0°C in winter in northern regions. And the raw materials of these stabilizers are widely available, easy to obtain, and have little impact on the environment. Finally, the optimized polysilicate aluminum chloride flocculant is applied to the treatment of tap water source water at 0°C in winter in northern regions. Experiments have shown that compared with polysilicate aluminum chloride without adding stabilizers, after adding stabilizers, the flocculation performance remains stable, and the stable treatment of 0°C low-temperature and low-turbidity tap water source water is achieved, ensuring that the water quality meets the standards. The present invention has achieved remarkable improvements in the synthesis process, stability improvement and practical application of the polyaluminium silicate chloride flocculant, and provides a new solution for the treatment of tap water sources in winter. DETAILED DESCRIPTION

[0025] The present invention provides a method for preparing a polyaluminium chloride silicate flocculant, comprising:

[0026] Step 1: Add the acid solution to the sodium silicate aqueous solution, and adjust the pH value to 3.0-4.0, stir and activate, and then let it stand. The stirring and activation time is preferably 10min-30min, and the standing time is preferably 10-30min, to obtain a polysilicic acid solution; the sodium silicate aqueous solution is obtained by dissolving sodium silicate nonahydrate in water, and the SiO2% content in the sodium silicate aqueous solution is preferably 2.0%. The present invention selects a suitable acid to accurately adjust the pH value according to the characteristics of the anions in the aluminum salt, thereby ensuring the stability of the flocculant. The acid solution is preferably hydrochloric acid.

[0027] Step 2: Add the polyaluminium chloride solution to the polysilicic acid solution, heat and stir at high speed, the heating temperature is preferably 65-75°C, the stirring speed is preferably 900-1100r / min, and the stirring time is preferably 30-60min, to obtain a polyaluminium silicate chloride solution; the polyaluminium chloride solution is preferably added according to an Al / SiO2 molar ratio of 1.0-2.0, more preferably a molar ratio of 1.5.

[0028] Step 3: Add a stabilizer to the polyaluminium silicate chloride solution obtained in step 2, and place it aside for aging to obtain a polyaluminium silicate chloride flocculant. The aging time is preferably 90-120 minutes, and the stabilizer is a solid stabilizer or a liquid stabilizer.

[0029] The fixed stabilizer preferably includes one or more of disodium hydrogen phosphate, sodium citrate or potassium hydrogen phthalate, and the added amount of the solid stabilizer is 7%-65% of the mass of the sodium silicate nonahydrate.

[0030] The liquid stabilizer preferably includes one or more of 10% NaOH solution, saturated sodium acetate solution, 0.1 mol / L potassium hydrogen phthalate solution or saturated sodium bicarbonate solution, and the added amount of the liquid stabilizer is 0.06-0.6 times the volume of the sodium silicate nonahydrate.

[0031] The present invention is further described in detail below with reference to specific examples, and the raw materials involved in the examples are all commercially available.

[0032] Example 1

[0033] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 50mL of 10% NaOH solution, stir and mix evenly, let stand for aging for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0034] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 3 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. It is found that the average turbidity of 0℃ tap water source water is 0.41NTU.

[0035] Example 2

[0036] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 26mL of saturated sodium acetate solution, stir and mix evenly, let stand for 120min, and obtain a polysilicate aluminum chloride flocculant.

[0037] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 22 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.46NTU.

[0038] Example 3

[0039] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 0.738g of disodium hydrogen phosphate, stir and mix evenly, let stand for aging for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0040] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 8 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.47NTU.

[0041] Example 4

[0042] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 2.952g of disodium hydrogen phosphate, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0043] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 10 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.47NTU.

[0044] Example 5

[0045] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 5.9g of disodium hydrogen phosphate and 1.6g of sodium citrate, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0046] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 25 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.63NTU.

[0047] Example 6

[0048] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 120mL of 0.1mol / L potassium hydrogen phthalate solution, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0049] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 9 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.47NTU.

[0050] Example 7

[0051] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool. Add 2.35g of potassium hydrogen phthalate, stir and mix evenly, let stand for aging for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0052] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 8 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source is 0.48NTU.

[0053] Example 8

[0054] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 26mL of saturated sodium bicarbonate, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0055] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 2 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. It is found that the average turbidity of 0℃ tap water source water is 0.74NTU.

[0056] Example 9

[0057] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 13mL of saturated sodium bicarbonate, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0058] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this embodiment has a stabilization time of 3 days. The turbidity standard of domestic drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. It is found that the average turbidity of 0℃ tap water source water is 0.74NTU.

[0059] Comparative Example 1

[0060] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with sulfuric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 50mL of 10% NaOH solution, stir and mix evenly, let stand for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0061] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured every 24h. The stability time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the stability time of the polysilicate aluminum chloride flocculant in this comparative example is only 1 day. The turbidity standard of drinking water is 1NTU, and the turbidity of 0℃ tap water source water is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source water. According to the experimental scheme for testing the stability time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0℃ tap water source water is 0.46NTU. The results show that compared with Example 1, the use of sulfuric acid to adjust the pH cannot extend the stability time of polysilicate aluminum chloride.

[0062] Comparative Example 2

[0063] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 70℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 20mL of 10% NaOH solution, stir and mix evenly, let stand for aging for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0064] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this comparative example has a stabilization time of only 1 day. The turbidity standard for drinking water is 1NTU, and the turbidity of 0℃ tap water source is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. It is found that the average turbidity of 0℃ tap water source is 0.45NTU.

[0065] Comparative Example 3

[0066] Add 9.32g of sodium silicate nine hydrate into a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let it stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let it stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat it at 70℃ and stir it at high speed, the stirring speed is 1000r / min, the stirring time is 60min, let it stand to cool down, and obtain a polysilicic acid aluminum chloride flocculant.

[0067] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polyaluminum silicate chloride, which is prepared and used immediately, the stabilization time of the polyaluminum silicate chloride flocculant in this comparative example is only 1 day. The turbidity standard for drinking water is 1NTU, and the turbidity of 0°C tap water source is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of the 0°C tap water source is 0.46NTU. Compared with Comparative Example 2 and Example 1, no stabilizer is added to this comparative example. The results show that the stabilization time cannot be extended by not adding or adding less stabilizer.

[0068] Comparative Example 4

[0069] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 1.0-2.0 with hydrochloric acid, stir and activate for 15min, and let it stand for 10min to obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water and let it stand for 30min to obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat it at 70℃ and stir it at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let it stand to cool down. Add 2.952g of disodium hydrogen phosphate, stir and mix evenly, and let it stand for aging for 120min. After the product is synthesized, add it to the tap water source water, and use a turbidity meter to test its turbidity. It is found that the turbidity of the tap water source water at 0℃ is 2.94NTU.

[0070] Comparative Example 5

[0071] 9.32g of sodium silicate nine hydrate was added to a 500mL beaker, dissolved in 200mL of distilled water to obtain a sodium silicate solution, stirred and activated for 15min, and allowed to stand for 10min to obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, 6.56g of aluminum chloride was dissolved in distilled water and allowed to stand for 30min to obtain a polyaluminum chloride solution. Then it was added to the polysilicic acid solution to produce a gel, which failed to achieve the purpose of synthesis.

[0072] Comparative Example 6

[0073] Add 9.32g of sodium silicate nine hydrate to a 500mL beaker, dissolve it with 200mL of distilled water to obtain a sodium silicate solution, adjust the pH range to 3.0-4.0 with hydrochloric acid, stir and activate for 15min, let stand for 10min, and obtain a polysilicic acid solution. According to the Al / SiO2 molar ratio of 1.5, dissolve 6.56g of aluminum chloride in distilled water, let stand for 30min, and obtain a polyaluminum chloride solution. Then add it to the polysilicic acid solution, heat at 60℃ and stir at high speed, the stirring speed is 1000r / min, the stirring time is 60min, and let stand to cool down. Add 5.9g of disodium hydrogen phosphate and 1.6g of sodium citrate, stir and mix evenly, let stand for aging for 120min, and obtain a polysilicic acid aluminum chloride flocculant.

[0074] After the product is synthesized, the product is added to the tap water source at intervals of 0h, 6h, and 24h, and the turbidity of the tap water source is measured by a turbidity meter, and then measured once every 24h, and the stabilization time is finally obtained. Compared with the original polysilicate aluminum chloride, which is prepared and used immediately, the polysilicate aluminum chloride flocculant of this comparative example has a stabilization time of 18 days. The turbidity standard for drinking water is 1NTU, and the turbidity of 0°C tap water source is 3.0-4.0NTU. The product is synthesized three times and added to the tap water source. According to the experimental scheme for testing the stabilization time, the turbidity is tested using a turbidity meter, and the average value is taken. The average turbidity of 0°C tap water source is 0.74NTU. Compared with Example 5, the average turbidity is slightly increased. The experimental results show that the optimal reaction temperature is 70°C.

Claims

1. A method for preparing a polyaluminium silicate chloride flocculant, characterized in that: include: Step 1: adding the acid solution to the sodium silicate aqueous solution, adjusting the pH value, stirring and activating, and then standing to obtain a polysilicic acid solution; Step 2: adding the polyaluminium chloride solution to the polysilicic acid solution, heating and stirring at high speed to obtain a polysilicic acid aluminium chloride solution; Step 3: adding a stabilizer to the polyaluminium chloride solution obtained in step 2 to obtain a polyaluminium chloride flocculant.

2. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The acid solution described in step 1 is hydrochloric acid.

3. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The SiO2% content in the sodium silicate aqueous solution described in step 1 is 2.0%.

4. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The pH value of step 1 is controlled at 3.0-4.

0.

5. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The stirring activation time in step 1 is 10 min to 30 min.

6. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: In step 2, the polyaluminium chloride solution is added according to the Al / SiO2 molar ratio of 1.0-2.

0.

7. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The heating temperature in step 2 is 65-75° C., and the stirring speed is 900-1100 r / min.

8. The method for preparing a polyaluminium chloride flocculant according to claim 1, characterized in that: The stabilizer in step three is a solid stabilizer or a liquid stabilizer.

9. The method for preparing a polyaluminium chloride flocculant according to claim 8, characterized in that: The fixing stabilizer includes one or more of disodium hydrogen phosphate, sodium citrate or potassium hydrogen phthalate.

10. The method for preparing a polyaluminium chloride flocculant according to claim 8, characterized in that: The liquid stabilizer comprises one or more of 10% NaOH solution, saturated sodium acetate solution, 0.1 mol / L potassium hydrogen phthalate solution or saturated sodium bicarbonate solution.